Ultrasonication-Assisted Spray Ionization Mass Spectrometry for the Analysis of Biomolecules in Solution - Chen, Tsung-Yi; Lin, Jia-Yi; Chen, Jen-Yi; Chen, Yu-Chie (My University, 2010)
In this paper, we describe a novel technique-ultrasonication-assisted spray ionization (UASI) for the generation of singly charged and multiply charged gas-phase ions of biomolecules (e.g., amino acids, peptides, and proteins) from solution; this method employs a low-frequency ultrasonicator (ca. 40 kHz) in place of the high electric field required for electrospray ionization. When a capillary inlet is immersed into a sample solution within a vial subjected to ultrasonication, the solution is continually directed to the capillary outlet as a result of ultrasonication-assisted capillary action; an ultrasonic spray of the sample solution is emitted at the outlet of the tapered capillary, leading to the ready generation of gas-phase ions. Using an ion trap mass spectrometer, we found that singly charged amino acid and multiply charged peptides/proteins ions were generated through this single-step operation, which is both straightforward and extremely simple to perform. The setup is uncomplicated: only a low-frequency ultrasonicator and a tapered capillary are required to perform UASI. The mass spectra of the multiply charged peptides and proteins obtained from sample solutions subjected to UASI resemble those observed in ESI mass spectra. (J Am Soc Mass Spectrom 2010, 21, 1547-1553) (C) 2010 American Society for Mass Spectrometry